Guided Mode Analysis and Characteristic of Bragg Optical Fibers - Kaewrawang, Arkom; Angkaew, Tuptlm (Engineering and Applied Science Research, 2015)
This paper presents the analysis of guided mode of a Bragg optical tiber which tinite pairs of cladding using the exact method. Consequently, the guided modes are corresponding to the Bragg optical fiber in practical. The computational results from this method are compare with the computational results from the analysis of guided mode of a Bragg optical tiber which intinite pairs of cladding using the asymptotic matrix method. In addition, this paper is demonstrate some examples of the analysis, electromagnetic field distribution, radiation loss, dispersion parameter of an air core Bragg optical tiber. The computational results have been found that the most of electromagnetic field of the lower order mode are in the air core, the radiation loss is depend on the pairs of cladding and the mode, and the dispersion of the Bragg optical fiber is higher than the dispersion of the conventional fiber.